Energy Consumption on Tillage Operation in Low Land Paddy Cultivation. (September 2019) - Lubis, M I A; Putri, R E; Andasuryani; Santosa; Arlius, F; Hasan, A
Abstract: Energy consumption is important to know for efficient on using energy. This study is determined using energy for tillage operation in low land paddy cultivation in Padang Pariaman, West Sumatera Province. The aims of this study is to identify any energy expenditure which used for tillage operation. The data were collected in five paddy field which was located at 0°40′41.63″ - 0°40′37.15″ latitude and 100°16′39.64″ - 100°16′46.38″ longitude and average areas is 792.4 meters-square. The energy expenditure were collected on tillage operation which are machinery, fuel, and human energy. All of the energy expenditure will be calculating by manual calculation (conversion factor of energy), exception human energy it also calculating by realtime measurement equipment ( Garmin Forerunner 35 ). The biggest consumption energy occured at fuel energy and the lowest one is machinery energy. The fuel energy were 270.6195 and 314.6556 MJ/ha for the average of fuel energy on first and secondary tillage operation, respectively. For first and secondary tillage operation, the average energy of machine were 6.6683 and 9.2414 MJ/ha, respectively. Human energy shown the average energy expenditure on first and secondary tillage operation were 19.4979 and 24.5826 MJ/ha by equipment, while the energy calculation uses conversion factor were 14.8358 and 19.4979 MJ/ha.